0316 Estimating Personal Exposure to Traffic-Related Air Pollutants among On-Road Workers0316 Estimating Personal Exposure to Traffic-Related Air Pollutants among On-Road Workers. (23rd June 2014) - Almberg, Kirsten; Hepler, Jordan; Sietsema, Margaret; Schmitz, Matthew; Conroy, Lorraine
Abstract : Objectives: Many individuals in the U.S. work in close proximity to traffic-related air pollution. Often these jobs require physical activity which increases breathing rate and results in higher personal exposures to pollutants. The goal of this study was to systematically estimate and characterise personal exposure to traffic-related pollutants for those working on or near roadways. Method: Concentrations of elemental carbon, carbon monoxide, and PM2.5 were measured along six traffic routes in the City of Chicago. These routes represent varying levels of exposure to traffic-related pollutants. Measurements were taken during peak and off-peak traffic hours during the summer and fall. All measurements were obtained from environmental monitoring equipment affixed to the back of a bicycle. Results: Air pollutant levels varied significantly across routes and time of day. Mean carbon monoxide levels ranged from 0.006–1.653 ppm across the sampling events. The geometric mean elemental carbon level was 1.75 µg/m 3 and ranged from 0.23 to 8.38 µg/m 3 . The geometric mean PM2.5 level was 39 µg/m 3 and ranged from 16 to 270 µg/m 3 . Levels of elemental carbon and PM2.5 were significantly higher during peak traffic samples than off-peak traffic samples. Conclusions: This study uses novel methods to estimate exposure to those who are physically active along roadways including mobile. While there is considerable time and route variation in air pollutant measurement, the levels of air pollutants measured in this study may have serious health implications for those who perform physically demanding activities near or on roadways in the City of Chicago.